Podstawowe tezy teorii naznaczania społecznego - Krajewski, Krzysztof (Wydział Prawa i Administracji UAM, 1983)
The theory of social labelling has radically revaluated several propositions previously widely accepted in the sociology of deviations and in criminology. It is mostly a question of the departure from the deterministic approach giving preference to the etiology analysis of deviational and criminal phenomena combined with a stress on the role of social control understood as a factor being at the bottom of social order. The theory has also criticized discriminating deviational and criminal phenomena from other social facts on the grounds of their objective and qualitative differences, The proposition of "distinctness" of deviated persons or criminals from other people, which was in addition to account for deviational behaviour, was pronouncedly dismissed. A new way of defining the deviational phenomena was developed in the social labelling theory upon application of the behavioral criterion of reaction to a given type of behaviour in place of the previous formal criterion of a norm contravention. Simultaneously a, stress was laid on the role of an intragroup interaction in forming judgements and interpretations of other persons behaviour and in considering it to be deviated. Reflections on the negative effect of the institution of social control were extended by introducing a notion of the secondary deivation. Consequently it was suggested in the new trend to reevaluate the previous treatment of deviational and criminal phenomena and replacing the "correctional" attitude with the one of "understanding". That would imply a substantial change in methods and ways of treating phenomena of deviation and deviated persons themselves. To sum up: irrespective of the disputability of its several propositions, the social labelling theory can be considered as a particularly original attempt at creating a complimentary approach to the subject in relation to the previous theories of deviation and crime.
Essential propositions of the social labelling theory